1984
DOI: 10.1287/mnsc.30.12.1389
|View full text |Cite
|
Sign up to set email alerts
|

Introduction Strategy for New Products with Positive and Negative Word-of-Mouth

Abstract: Existing innovation diffusion models assume that individual experience with the product is always communicated positively through word-of-mouth. For certain innovations, however, this assumption is tenuous since communicators of the product experience may transfer favorable, unfavorable, or indifferent messages through word-of-mouth. This paper examines a diffusion model for products in which negative information plays a dominant role, discusses its implications for optimal advertising timing policy and presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
164
0
7

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(174 citation statements)
references
References 16 publications
1
164
0
7
Order By: Relevance
“…Clearly, the effect on success would depend on the valence of the information communicated, positive or negative (e.g., Mahajan et al 1984), where the valence depends on the reputation of the developers. As in the case of corporate reputation (e.g., Fombrun and Shanley 1990), reputation in the open source environment should be a multidimensional construct.…”
Section: Hypothesis 3b (H3b) the Likelihood That Project Manager Embmentioning
confidence: 99%
“…Clearly, the effect on success would depend on the valence of the information communicated, positive or negative (e.g., Mahajan et al 1984), where the valence depends on the reputation of the developers. As in the case of corporate reputation (e.g., Fombrun and Shanley 1990), reputation in the open source environment should be a multidimensional construct.…”
Section: Hypothesis 3b (H3b) the Likelihood That Project Manager Embmentioning
confidence: 99%
“…Research in marketing generally supports the claim that WOM is more influential on behavior than other marketer-controlled sources (Day, 1971;Sheth, 1971;Mahajan, Muller, & Kerin, 1984). WOM has been shown to influence a variety of conditions: awareness, expectations, perceptions, attitudes, and behavior (Richins & Root-Shaffer, 1988;Hogan et al, 2004).…”
Section: Word Of Mouthmentioning
confidence: 87%
“…Mahajan et al (1984) showed that when there is a negative rumor in the release of a certain product, the most appropriate strategy is to increase and change the level of consumers' awareness through advertising as soon as possible.…”
Section: Positive and Negative Wommentioning
confidence: 99%
“…1 Especially when they have already ordered the product and know for sure that they will be delivered before the consumers ordering it later on 2 Some diffusion models have reported negative word-of-mouth effect for new products [38,39]. However, we do not believe this is likely to occur in this first phase of the model since committed consumers have not experienced the product yet.…”
Section: Credibility Factormentioning
confidence: 98%